Analysis of Science Problem Solving Ability in terms of Learning Style of Junior High School Students - Syahrin, Rania Alfi; Putri, Amelia Nabila; Inayah, Nailil; Prahani, Binar Kurnia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This study aims to identify students' learning styles, assess their science problem-solving abilities, and analyze these abilities in relation to their learning styles on the topics of vibration, wave, and sound. Employing a quantitative descriptive approach, data were collected through tests, observations, and interviews. Instruments included a learning style questionnaire, problem-solving ability test, and interview guidelines. The findings reveal four learning styles among students—visual (25%), auditory (13%), kinesthetic (58%), and visual-kinesthetic (4%)—with kinesthetic being the most prevalent. However, 71% of students demonstrated low science problem-solving ability, with an average score of 52.9. Specifically, problem-solving performance was categorized as low across all four indicators: understanding the problem (36.5%), planning the solution (29.2%), implementing the solution (29.7%), and rechecking the answer (18.3%). Students with visual learning styles performed better in all problem-solving stages compared to their auditory and kinesthetic peers. This study highlights the need for tailored teaching strategies to improve problem-solving skills, particularly for students with auditory and kinesthetic learning styles, as no prior research has focused on the interplay between learning styles and problem-solving abilities in the context of vibration, wave, and sound materials.